Bismuth layered sodium bismuth titanate high temperature piezoelectric ceramic material and its preparation method and application
By ionic replacement of Nb and Sr elements on bismuth layered sodium bismuth titanate high-temperature piezoelectric ceramic materials, and adjusting their components and preparation processes, the problems of low piezoelectric properties and large deviations in high temperature sensitivity of existing materials are solved, and the effect of high voltage electrical properties, maintaining high Curie temperature and high temperature resistivity is achieved.
Patent Information
- Application Number
- CN202510000653.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-02
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-01-02
AI Technical Summary
The spontaneous polarization of existing bismuth-layered sodium bismuth titanate high-temperature piezoelectric ceramic materials is limited by two-dimensionality, with low piezoelectric properties, and large sensitivity deviations at high temperatures, making it difficult to simultaneously improve piezoelectric properties and maintain high Curie temperature and high temperature resistivity.
By ionic substitution of the bismuth-layered structure bismuth sodium titanate piezoelectric ceramic material (Na0.5Bi4.5Ti4O15 ceramic) of bismuth layered structure (Na0.5Bi4.5Ti4O15 ceramic) and adjusting its components, a specific preparation method is adopted, including ball milling, prefixing, grinding, granulation, molding and sintering of mixed raw materials, a bismuth layered bismuth sodium titanate high-temperature piezoelectric ceramic material of Na0.5Bi4.5Ti4-xNbxO15+x/2:Sr is prepared.
It effectively improves the piezoelectric properties of bismuth layered bismuth titanate high-temperature piezoelectric ceramic materials, while maintaining high Curie temperature and excellent high-temperature resistivity, and is suitable for the field of high-temperature piezoelectric devices.
Smart Images

Figure CN119390441B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of high-temperature piezoelectric ceramic materials, and in particular relates to a bismuth layered sodium bismuth titanate high-temperature piezoelectric ceramic material and a preparation method and application thereof. Background Art
[0002] Piezoelectric materials have been widely used in many devices such as sensors, actuators, transducers and energy harvesters due to their mutual conversion characteristics between electrical energy and mechanical energy. In recent years, with the rapid development of aerospace, automotive industry and energy exploration, the demand for high-temperature piezoelectric materials has become increasingly urgent, so the research on high-temperature piezoelectric materials is of great significance.
[0003] As a piezoelectric material, bismuth layered ceramics usually have ultra-high Curie temperature, high mechanical quality factor, excellent insulation resistance and withstand voltage characteristics, and anisotropy due to their unique layered structure. They have broad application prospects in high-temperature and high-frequency applications. 0.5 Bi 4.5 Ti4O 15 The Curie temperature of ceramics is as high as 657°C, which has great advantages in the high-temperature field, but its spontaneous polarization is limited by two dimensions. 33 It is only about 16 pC / N, which limits its application to a certain extent. Although a lot of research is devoted to improving its piezoelectric properties through process improvement and component optimization, the Curie temperature and high temperature resistivity are reduced to a certain extent, and the use of Na 0.5 Bi 4.5 Ti4O 15 The sensitivity of ceramic sensors at high temperatures generally deviates greatly. Therefore, it is necessary to explore the method that can effectively increase the Na 0.5 Bi 4.5 Ti4O 15 Methods to improve the piezoelectric properties of ceramics without reducing their Curie temperature and high-temperature resistivity have become an important research topic in this field. Summary of the invention
[0004] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a bismuth-layered sodium bismuth titanate high-temperature piezoelectric ceramic material, which effectively improves the piezoelectric performance while maintaining a high Curie temperature and excellent high-temperature resistivity.
[0005] Another object of the present invention is to provide a method for preparing a bismuth layered sodium bismuth titanate high temperature piezoelectric ceramic material. The preparation method comprises the following steps: using Nb and Sr elements to prepare a bismuth layered sodium bismuth titanate piezoelectric ceramic material (Na 0.5 Bi 4.5 Ti4O 15Ceramics) are doped and modified.
[0006] Another object of the present invention is to provide a bismuth layered sodium bismuth titanate high-temperature piezoelectric ceramic material for use in an acceleration sensor.
[0007] The purpose of the present invention is achieved through the following technical solutions.
[0008] A bismuth layered sodium bismuth titanate high temperature piezoelectric ceramic material, wherein the general formula of the bismuth layered sodium bismuth titanate high temperature piezoelectric ceramic material is Na 0.5 Bi 4.5 Ti 4-x Nb x O 15+x / 2 :Sr, calculated by the amount of substance, Sr and Na 0.5 Bi 4.5 Ti 4-x Nb x O 15+x / 2 The ratio is 0.02:1, 0.04≤x≤0.08.
[0009] A method for preparing a bismuth layered sodium bismuth titanate high-temperature piezoelectric ceramic material comprises the following steps:
[0010] Step 1, mixing a Na source, a Bi source, a Ti source, a Nb source and a Sr source, ball milling to obtain a mixed raw material, pre-sintering the mixed raw material at 750-800 ° C for 2-4 h, cooling to room temperature to obtain a pre-sintered powder, wherein, by amount of substance, the ratio of Na in the Na source, Bi in the Bi source, Ti in the Ti source, Nb in the Nb source and Sr in the Sr source is 0.5:4.5:(4- x ): x : 0.02;
[0011] In step 1, the Na source is Na2CO3, the Bi source is Bi2O3, the Ti source is TiO2, the Nb source is Nb2O5, and the Sr source is SrCO3.
[0012] In step 1, the temperature is raised to 750-800°C at a rate of 3-5°C / min.
[0013] Step 2, grinding, sieving, secondary ball milling, granulating, and molding the pre-sintered powder to obtain a blank;
[0014] In the step 2, the granulation binder is a polyvinyl alcohol (PVA) solution, the polyvinyl alcohol solution is a mixture of polyvinyl alcohol and water, and the concentration of polyvinyl alcohol in the polyvinyl alcohol solution is 5-7wt%.
[0015] In the granulation of step 2, the polyvinyl alcohol solution is 7-10wt% of the pre-sintered powder.
[0016] In step 1 and step 2, the ball milling is wet milling, the medium of wet milling is anhydrous ethanol, and the ball milling beads are agate balls.
[0017] In the above technical solution, after wet grinding, the product is first dried, then ground, and finally sieved.
[0018] In step 1 and step 2, the drying temperature is 80-100° C., and the drying time is 3-5 hours.
[0019] In step 1 and step 2, the ball milling time is 6 to 8 hours, and the ball milling speed is 250 to 300 r / min.
[0020] In the ball milling of step 1, the ratio of the agate balls, the mixed raw materials and anhydrous ethanol is (0.8-1.0): (0.6-0.7): (0.5-0.7) by mass.
[0021] In step 2, the molding operation includes: firstly using a tablet press to press into a columnar embryonic body, and then molding in a cold isostatic press.
[0022] In the above technical solution, the pressure for pressing the embryo into a columnar shape is 2-5 MPa, and the time for pressing the embryo into a columnar shape is 30-60 seconds.
[0023] In the above technical solution, the molding pressure in the cold isostatic press is 280~300Mpa and the molding time is 10~30s.
[0024] In step 1 and step 2, the sieve has a mesh size of 60 to 80.
[0025] Step 3, debinding the blank, sintering at 1050-1090°C for 3-5h to obtain a ceramic column, slicing to obtain a ceramic sheet, and successively subjecting the ceramic sheet to electrodes on both sides, electrode sintering, and polarization in silicone oil to obtain a bismuth layered sodium bismuth titanate high-temperature piezoelectric ceramic material.
[0026] In the step 3, the debinding includes: keeping the temperature at 550-600° C. for 2-4 hours and naturally cooling the temperature to room temperature.
[0027] In step 3, the heating rate of the debinding is 3-5°C / min.
[0028] In step 3, the thickness of the ceramic sheet is 0.6-0.8 mm.
[0029] In step 3, both sides of the ceramic sheet are treated with silver by screen printing.
[0030] In step 3, the electrode sintering temperature is 750-800° C., and the electrode sintering time is 20-30 minutes.
[0031] In step 3, the temperature of the silicone oil is 170-200° C., the polarization field strength is 8-10 kV / mm, and the polarization time is 20-30 min.
[0032] Application of the above-mentioned bismuth layered sodium bismuth titanate high-temperature piezoelectric ceramic material in acceleration sensors.
[0033] Compared with the prior art, the present invention has the following beneficial effects:
[0034] (1) The preparation method of the present invention selects Nb and Sr elements to form a bismuth layered sodium bismuth titanate piezoelectric ceramic material (Na 0.5 Bi 4.5 Ti4O 15 Ceramics) ion substitution (for Bi 3+ and Ti 4+ Partial ion substitution) is carried out, while ensuring a high Curie temperature, the piezoelectric properties and resistivity of the bismuth layered sodium bismuth titanate high-temperature piezoelectric ceramic material are improved. The dielectric loss of the bismuth layered sodium bismuth titanate high-temperature piezoelectric ceramic material is 0.0037, the Curie temperature is 669°C, the piezoelectric constant is 31.5pC / N, and the mechanical quality factor is Q m is 3576, the electromechanical coupling coefficient k p The high temperature resistivity is 15.2% and the high temperature resistivity is 5.7*10 at 500℃. 7 Ω·cm, bismuth layered sodium bismuth titanate high-temperature piezoelectric ceramic materials have broad application prospects in the field of high-temperature piezoelectric devices.
[0035] (2) The preparation method of the present invention has simple process, low cost, is suitable for large-scale industrial production, and has broad application prospects.
[0036] (3) The high-temperature acceleration sensor assembled with the bismuth layered sodium bismuth titanate high-temperature piezoelectric ceramic material of the present invention as the core component has a sensitivity deviation within ±5% in the range of room temperature to 500°C, and an impedance of up to 10 7 , can work stably at 500 ℃. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 XRD patterns of bismuth layered sodium bismuth titanate high temperature piezoelectric ceramic materials prepared in Example 2, Example 6, Example 10, Example 14 and Example 18;
[0038] Figure 2are scanning electron microscope (SEM) images, wherein (a) is the bismuth layered sodium bismuth titanate high temperature piezoelectric ceramic material prepared in Example 2, (b) is the bismuth layered sodium bismuth titanate high temperature piezoelectric ceramic material prepared in Example 6, (c) is the bismuth layered sodium bismuth titanate high temperature piezoelectric ceramic material prepared in Example 10, (d) is the bismuth layered sodium bismuth titanate high temperature piezoelectric ceramic material prepared in Example 14, and (e) is the bismuth layered sodium bismuth titanate high temperature piezoelectric ceramic material prepared in Example 18;
[0039] Figure 3 This is a graph showing the change in dielectric constant of the bismuth layered sodium bismuth titanate high-temperature piezoelectric ceramic material prepared in Example 14 as a function of temperature;
[0040] Figure 4 The piezoelectric constant of the bismuth layered sodium bismuth titanate high temperature piezoelectric ceramic material prepared in Example 2, Example 6, Example 10, Example 14, Example 18 and Comparative Examples 1-2 varies with temperature;
[0041] Figure 5 The resistivity of the bismuth layered sodium bismuth titanate high temperature piezoelectric ceramic materials prepared in Example 2, Example 6, Example 10, Example 14, Example 18 and Comparative Examples 1-2 varies with temperature;
[0042] Figure 6 It is a cross-sectional view of a compression-type piezoelectric high-temperature acceleration sensor (the plug is located on the side of the shell);
[0043] Figure 7 It is a cross-sectional view of a compression-type piezoelectric high-temperature accelerometer (the plug is located on the top surface of the shell).
[0044] Among them, 1: shell, 2: plug, 3: core, 3-1: base, 3-2: mass block, 3-3: electrode sheet, 3-4: insulating sheet, 3-5: ceramic sheet, 3-6: column, 3-7: fastening device. DETAILED DESCRIPTION
[0045] The technical solution of the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments.
[0046] In the following examples, Na2CO3, Bi2O3, TiO2, Nb2O5 and SrCO3 were all analytically pure.
[0047] Embodiments 1 to 20
[0048] A method for preparing a bismuth layered sodium bismuth titanate high-temperature piezoelectric ceramic material comprises the following steps:
[0049] Step 1, Na source, Bi source, Ti source, Nb source and Sr source are placed in a ball mill and mixed evenly to obtain a mixed raw material, anhydrous ethanol and ball milling beads (agate balls) are added to the mixed raw material, the mass ratio of agate balls, mixed raw materials and anhydrous ethanol is 1.0:0.7:0.5, ball milling is performed at 300 r / min for 8 hours, and after ball milling, the mixture is dried in an oven at 100°C for 5 hours, ground with a mortar, and passed through a 60-mesh sieve. The sieved powder is placed in an alumina crucible, compacted, covered, and sealed with zirconium oxide powder to prevent the volatilization of the Bi source, and the sealed alumina crucible is placed in a muffle furnace and heated to 800°C at a rate of 5°C / min and pre-calcined at 800°C for 3 hours. h, naturally cooling to room temperature to obtain a pre-sintered powder, wherein, by amount, the ratio of Na in the Na source, Bi in the Bi source, Ti in the Ti source, Nb in the Nb source and Sr in the Sr source is D, the Na source is Na2CO3, the Bi source is Bi2O3, the Ti source is TiO2, the Nb source is Nb2O5 and the Sr source is SrCO3;
[0050] Step 2, grind the pre-sintered powder, pass it through a 60-mesh sieve, perform secondary ball milling at 300 r / min for 8 hours, dry it at 100 ° C for 5 hours after ball milling, grind it, pass it through a 60-mesh sieve, granulate the sieved powder with a 5wt% polyvinyl alcohol (PVA) solution (the polyvinyl alcohol solution is a mixture of polyvinyl alcohol and water), the polyvinyl alcohol solution is 9wt% of the pre-sintered powder, take 7g of the granulated powder and place it in a mold with a diameter of 13mm, press it into a columnar embryo body in a tablet press with a pressure of 2Mpa for 30s, and then press it in a cold isostatic press with a pressure of 300Mpa for 10s to obtain an embryo;
[0051] Step 3, heat the blank to 600℃ at a heating rate of 5℃ / min and debind at 600℃ for 2h, cool it naturally to room temperature, sinter it at W℃ for 3h to obtain a ceramic column, slice it to obtain a ceramic sheet with a thickness of 0.6mm, use screen printing to silver-treat both sides of the ceramic sheet (electrode), sinter it at 800℃ for 20min, and after sintering, polarize it in 190℃ silicone oil with a polarization field strength of 10kV / mm for 30min to obtain a bismuth layered sodium bismuth titanate high-temperature piezoelectric ceramic material.
[0052] The D and W of the bismuth layered sodium bismuth titanate high temperature piezoelectric ceramic materials prepared in Examples 1 to 20 are shown in Table 1.
[0053] Table 1
[0054]
[0055] Comparative Example 1
[0056] A method for preparing a bismuth layered sodium bismuth titanate high-temperature piezoelectric ceramic material is basically the same as Example 14, with the only difference being: mixed raw materials. In Comparative Example 1, the mixed raw materials are Na source, Bi source, Ti source and Nb source. Calculated by the amount of substance, the ratio of Na in the Na source, Bi in the Bi source, Ti in the Ti source and Nb in the Nb source is 0.5:4.5:3.94:0.06.
[0057] Comparative Example 2
[0058] A method for preparing a bismuth layered sodium bismuth titanate high-temperature piezoelectric ceramic material is basically the same as Example 14, with the only difference being: mixed raw materials. In Comparative Example 2, the mixed raw materials are Na source, Bi source, Ti source, Nb source and Sr source. Calculated by the amount of substance, the ratio of Na in the Na source, Bi in the Bi source, Ti in the Ti source, Nb in the Nb source and Sr in the Sr source is 0.49:4.41:3.94:0.06:0.02.
[0059] Figure 1 The XRD patterns of the bismuth layered sodium bismuth titanate high temperature piezoelectric ceramic materials prepared in Examples 2, 6, 10, 14 and 18 are shown. Figure 1 It can be seen that the crystal plane index of the strongest peak in the XRD spectrum of the bismuth layered sodium bismuth titanate high temperature piezoelectric ceramic materials prepared in Example 2, Example 6, Example 10, Example 14 and Example 18 is (119), which is different from the bismuth layered sodium bismuth titanate piezoelectric ceramic material (Na 0.5 Bi 4.5 Ti4O 15 The crystal plane index (119) of the strongest peak of the piezoelectric ceramics (Example 2, Example 6, Example 10, Example 14 and Example 18) is consistent, indicating that the bismuth layered sodium bismuth titanate high-temperature piezoelectric ceramic materials prepared in Example 2, Example 6, Example 10, Example 14 and Example 18 are all typical bismuth layered orthorhombic structures.
[0060] The bismuth layered material has a bismuth layered orthogonal structure, and its surface energy along the c-axis direction is much lower than that along the ab plane, resulting in a much greater growth rate of its grains along the ab plane than along the c-axis direction. Generally, a relatively flat sheet structure is formed on the ab plane, and finally it appears as a flat grain. Scanning electron microscopy (SEM) was performed on the bismuth layered sodium bismuth titanate high temperature piezoelectric ceramic materials prepared in Examples 2, 6, 10, 14 and 18. Figure 2 As shown by Figure 2 It can be seen that the bismuth layered sodium bismuth titanate high-temperature piezoelectric ceramic materials prepared in Examples 2, 6, 10, 14 and 18 have good density, no large holes, and all show typical flat grains of bismuth layered materials.
[0061] At room temperature, the piezoelectric properties (piezoelectric constant d 33 , dielectric loss tan δ , Curie temperature T C , dielectric constant ε r , electromechanical coupling coefficient k p and mechanical quality factor Q m ), the test results are shown in Table 2.
[0062] Table 2
[0063]
[0064] It can be seen from Table 2 that compared with Comparative Examples 1-2, the piezoelectric constants ( d 33 ) are all improved, all above 20 pC / N, among which, the piezoelectric constant of the bismuth layered sodium bismuth titanate high-temperature piezoelectric ceramic material prepared in Example 14 is as high as 31.5 pC / N, and both maintain a good Curie temperature. Therefore, the bismuth layered sodium bismuth titanate high-temperature piezoelectric ceramic material prepared by the preparation method of the present invention has its piezoelectric constant ( d 33 ) have been improved.
[0065] Figure 3 The dielectric constant of the bismuth layered sodium bismuth titanate high temperature piezoelectric ceramic material prepared in Example 14 varies with temperature. Figure 3 It can be seen that the dielectric constant of the bismuth layered sodium bismuth titanate high-temperature piezoelectric ceramic material prepared in Example 14 is ε r It increases slowly in the range of room temperature to 500°C, increases sharply after 600°C to 669°C, and then decreases. Therefore, the bismuth layered sodium bismuth titanate high-temperature piezoelectric ceramic material prepared in Example 14 can be stably used in the range of 500°C.
[0066] Figure 4 The piezoelectric constant of the bismuth layered sodium bismuth titanate high temperature piezoelectric ceramic material prepared in Example 2, Example 6, Example 10, Example 14, Example 18 and Comparative Examples 1-2 varies with temperature. Figure 4 It can be seen that as the temperature increases, the piezoelectric constants ( d 33) is relatively stable. At 500°C, the piezoelectric constant of the bismuth layered sodium bismuth titanate high-temperature piezoelectric ceramic material of Example 14 is still maintained at 30.6pC / N, which can meet the application requirements at high temperatures.
[0067] Figure 5 The resistivity of the bismuth layered sodium bismuth titanate high temperature piezoelectric ceramic materials prepared in Example 2, Example 6, Example 10, Example 14, Example 18 and Comparative Examples 1-2 varies with temperature. Figure 5 It can be seen that at 500°C, the resistivity of the bismuth layered sodium bismuth titanate high-temperature piezoelectric ceramic material prepared in Example 2 is 9.0*10 5 Ω·cm, the resistivity of the bismuth layered sodium bismuth titanate high temperature piezoelectric ceramic material prepared in Example 6 is 1.2*10 7 Ω·cm, the resistivity of the bismuth layered sodium bismuth titanate high temperature piezoelectric ceramic material prepared in Example 10 is 3.6*10 7 Ω·cm, the resistivity of the bismuth layered sodium bismuth titanate high temperature piezoelectric ceramic material prepared in Example 18 is 4.2*10 7 Ω·cm, the resistivity of the bismuth layered sodium bismuth titanate high temperature piezoelectric ceramic material prepared in Comparative Example 1 is 6.0*10 6 Ω·cm, the resistivity of the bismuth layered sodium bismuth titanate high temperature piezoelectric ceramic material prepared in Comparative Example 2 is 4.6*10 6 Ω·cm, wherein the resistivity of the bismuth layered sodium bismuth titanate high temperature piezoelectric ceramic material prepared in Example 14 is still as high as 5.7*10 7 Ω·cm, the resistivity of the bismuth layered sodium bismuth titanate high temperature piezoelectric ceramic materials prepared in Example 10, Example 14 and Example 18 at high temperature is maintained at 10 7 cm, so it has great potential in high temperature applications.
[0068] Embodiment 21
[0069] The bismuth layered sodium bismuth titanate high-temperature piezoelectric ceramic material prepared in Example 14 is used as the core element (i.e., the piezoelectric element) to assemble a compression type piezoelectric high-temperature acceleration sensor. Figure 6 and Figure 7As shown, it includes: a core 3, a shell 1 and a plug 2, the shell 1 is a cavity, the core 3 is installed in the cavity, the plug 2 is fixed on the shell 1, the core 3 includes: a base 3-1, a mass block 3-2, N electrode sheets 3-3, two insulating sheets 3-4, a fastening device and N-1 ceramic sheets 3-5 (piezoelectric elements), the base 3-1 is used to be fixed with the shell 1, a column 3-6 is formed on the base 3-1, N electrode sheets 3-3, two insulating sheets 3-4 and N-1 ceramic sheets 3-5 are sleeved on the column 3-6, and each electrode sheet 3-3 is arranged horizontally. A ceramic sheet 3-5 is arranged between every two adjacent electrode sheets 3-3, an insulating sheet 3-4 is arranged above the uppermost electrode sheet 3-3 and below the lowermost electrode sheet 3-3, the mass block 3-2 is sleeved on the column 3-6 and located on the uppermost insulating sheet 3-4, the fastening device 3-7 is connected to the column 3-6 above the mass block 3-2, and is used to press N electrode sheets 3-3, two insulating sheets 3-4 and N-1 ceramic sheets 3-5 onto the base 3-1, for example: the fastening device 3-7 can be a bolt and is connected to the column 3-6 through a thread.
[0070] Preferably, the plug 2 is located on the top surface or side surface of the housing 1. Figure 6 As shown, the plug 2 is located on the side of the housing 1; Figure 7 As shown, the plug 2 is located on the top surface of the housing 1 .
[0071] Preferably, the N electrode sheets 3-3, the two insulating sheets 3-4 and the N-1 ceramic sheets 3-5 have the same structure, which is annular. In the present embodiment, the inner diameter of the ring is 4.2 mm and the outer diameter is 9.6 mm.
[0072] The thickness of each ceramic sheet 3-5 is 0.6 mm, and the ceramic sheet 3-5 is the bismuth layered sodium bismuth titanate high-temperature piezoelectric ceramic material prepared in Example 14;
[0073] Counting from top to bottom, the odd-numbered electrode sheets 3 - 3 are connected in series and connected to the positive pole of the plug 2 through a wire, and the even-numbered electrode sheets 3 - 3 are connected in series and connected to the negative pole of the plug 2 through a wire.
[0074] In this embodiment, N=6 or 7. The sensitivity and impedance performance of the compression type piezoelectric high temperature acceleration sensor were tested with a dynamic analyzer in the range of 25-500°C, and the test results are shown in Table 3. The results in Table 3 show that the sensitivity deviation of the compression type piezoelectric high temperature acceleration sensor of the present invention in the range of 25-500°C is within ±5%, and its impedance remains at 10 after being kept at 500°C for one hour. 7 Ω or above, which can ensure the stable charge output of the compression type piezoelectric high temperature acceleration sensor at a high temperature of 500℃.
[0075] Table 3
[0076]
[0077] The Chinese patent with publication number CN 112851336A discloses a high-temperature acceleration sensor prepared with sodium bismuth titanate high-temperature piezoelectric ceramic material as the piezoelectric element. In the range of room temperature to 400°C, its sensitivity decreases from 17.61 pC / g to 9.54 pC / g, and the sensitivity deviation is far more than ±5%. The sensitivity deviation will become larger and larger with the increase of temperature. In summary, the bismuth layered sodium bismuth titanate high-temperature piezoelectric ceramic material of the present invention has application prospects in acceleration sensors.
[0078] The present invention is described above by way of example. It should be noted that, without departing from the core of the present invention, any simple deformation, modification or other equivalent replacement that can be made by those skilled in the art without inventive effort falls within the protection scope of the present invention.
Claims
1. A bismuth layered sodium bismuth titanate high temperature piezoelectric ceramic material, characterized in that: The general formula of the bismuth layered sodium bismuth titanate high temperature piezoelectric ceramic material is Na 0.5 Bi 4.5 Ti 4-x Nb x O 15+x / 2 :Sr, calculated by the amount of substance, Sr and Na 0.5 Bi 4.5 Ti 4- x Nb x O 15+x / 2 The ratio is 0.02:1, x=0.06; the preparation method of the bismuth layered sodium bismuth titanate high temperature piezoelectric ceramic material comprises the following steps: Step 1, mixing a Na source, a Bi source, a Ti source, a Nb source and a Sr source, ball milling to obtain a mixed raw material, pre-sintering the mixed raw material at 750-800 ° C for 2-4 h, cooling to room temperature to obtain a pre-sintered powder, wherein, by amount of substance, the ratio of Na in the Na source, Bi in the Bi source, Ti in the Ti source, Nb in the Nb source and Sr in the Sr source is 0.5:4.5:(4- x ): x : 0.02; Step 2, grinding the pre-sintered powder, sieving, secondary ball milling, granulating, and molding to obtain a blank; Step 3, debinding the blank, sintering at 1050-1090°C for 3-5h to obtain a ceramic column, slicing to obtain a ceramic sheet, and successively subjecting the ceramic sheet to double-sided electrode sintering, electrode sintering, and polarization in silicone oil to obtain a bismuth layered sodium bismuth titanate high-temperature piezoelectric ceramic material.
2. The bismuth layered sodium bismuth titanate high temperature piezoelectric ceramic material according to claim 1, characterized in that: The Na source is Na2CO3, the Bi source is Bi2O3, the Ti source is TiO2, the Nb source is Nb2O5, and the Sr source is SrCO3.
3. The bismuth layered sodium bismuth titanate high temperature piezoelectric ceramic material according to claim 1, characterized in that: The binder for granulation is a polyvinyl alcohol solution, which is a mixture of polyvinyl alcohol and water, and the concentration of polyvinyl alcohol in the polyvinyl alcohol solution is 5-7wt%; the polyvinyl alcohol solution is 7-10wt% of the pre-sintered powder.
4. The bismuth layered sodium bismuth titanate high temperature piezoelectric ceramic material according to claim 1, characterized in that: The ball mill is wet milling, the medium of wet milling is anhydrous ethanol, and the ball milling beads are agate balls; after wet milling, it is first dried, then ground, and finally sieved; The ball milling time is 6-8 hours, and the ball milling speed is 250-300 r / min.
5. The bismuth layered sodium bismuth titanate high temperature piezoelectric ceramic material according to claim 1, characterized in that: The forming operation includes: firstly pressing into a cylindrical green body by a tablet press, and then forming in a cold isostatic press; The pressure for pressing the columnar blank is 2-5 MPa, and the time for pressing the columnar blank is 30-60 seconds; The molding pressure in the cold isostatic press is 280~300MPa and the time is 10~30s.
6. The bismuth layered sodium bismuth titanate high temperature piezoelectric ceramic material according to claim 1, characterized in that: The debinding process includes: keeping the temperature at 550-600° C. for 2-4 hours and naturally cooling the temperature to room temperature.
7. The bismuth layered sodium bismuth titanate high temperature piezoelectric ceramic material according to claim 1, characterized in that: The thickness of the ceramic sheet is 0.6-0.8 mm.
8. The bismuth layered sodium bismuth titanate high temperature piezoelectric ceramic material according to claim 1, characterized in that: The electrode sintering temperature is 750-800°C, and the electrode sintering time is 20-30 minutes; The temperature of the silicone oil is 170-200° C., the polarization field strength is 8-10 kV / mm, and the polarization time is 20-30 min.
9. A method for preparing bismuth layered sodium bismuth titanate high temperature piezoelectric ceramic material, characterized in that: The following steps are involved: Step 1, mixing a Na source, a Bi source, a Ti source, a Nb source and a Sr source, ball milling to obtain a mixed raw material, pre-sintering the mixed raw material at 750-800 ° C for 2-4 h, cooling to room temperature to obtain a pre-sintered powder, wherein, by amount of substance, the ratio of Na in the Na source, Bi in the Bi source, Ti in the Ti source, Nb in the Nb source and Sr in the Sr source is 0.5:4.5:(4- x ): x : 0.02, x=0.06; Step 2, grinding the pre-sintered powder, sieving, secondary ball milling, granulating, and molding to obtain a blank; Step 3, debinding the blank, sintering at 1050-1090°C for 3-5h to obtain a ceramic column, slicing to obtain a ceramic sheet, and successively subjecting the ceramic sheet to double-sided electrode sintering, electrode sintering, and polarization in silicone oil to obtain a bismuth layered sodium bismuth titanate high-temperature piezoelectric ceramic material.
10. The preparation method according to claim 9, characterized in that: The Na source is Na2CO3, the Bi source is Bi2O3, the Ti source is TiO2, the Nb source is Nb2O5, and the Sr source is SrCO3.
11. The preparation method according to claim 9, characterized in that: The binder for granulation is a polyvinyl alcohol solution, which is a mixture of polyvinyl alcohol and water, and the concentration of polyvinyl alcohol in the polyvinyl alcohol solution is 5-7wt%; the polyvinyl alcohol solution is 7-10wt% of the pre-sintered powder.
12. The preparation method according to claim 9, characterized in that: The ball mill is wet milling, the medium of wet milling is anhydrous ethanol, and the ball milling beads are agate balls; after wet milling, it is first dried, then ground, and finally sieved; The ball milling time is 6-8 hours, and the ball milling speed is 250-300 r / min.
13. The preparation method according to claim 9, characterized in that: The forming operation includes: firstly pressing into a cylindrical green body by a tablet press, and then forming in a cold isostatic press; The pressure for pressing the columnar blank is 2-5 MPa, and the time for pressing the columnar blank is 30-60 seconds; The molding pressure in the cold isostatic press is 280~300MPa and the time is 10~30s.
14. The preparation method according to claim 9, characterized in that: The debinding process includes: keeping the temperature at 550-600° C. for 2-4 hours and naturally cooling the temperature to room temperature.
15. The preparation method according to claim 9, characterized in that: The thickness of the ceramic sheet is 0.6-0.8 mm.
16. The preparation method according to claim 9, characterized in that: The electrode sintering temperature is 750-800°C, and the electrode sintering time is 20-30 minutes; The temperature of the silicone oil is 170-200° C., the polarization field strength is 8-10 kV / mm, and the polarization time is 20-30 min.
17. Use of the bismuth layered sodium bismuth titanate high temperature piezoelectric ceramic material according to claim 1 in an acceleration sensor.
Citation Information
Patent Citations
Preparation method of bismuth sodium bismuth titanate layered piezoelectric ceramic
CN112851336A